Wypowiedź ustna w dydaktyce językowej na przykładzie języka polskiego jako obcego - Janowska, Iwona (Księgarnia Akademicka Publishing, 2019)
This book falls within the field of language education and focuses on the shaping and developing of speaking competence in a foreign language. Reflection on teaching and learning speaking comprises two basic types of issues. The first of these includes deliberations of theoretical character, which are the subject matter of the first three chapters of the book. They introduce the key theories developed within theoretical and applied linguistics as well as psychological ideas about the very essence of language, its use, as well as teaching and learning. What is meant here is scientific theories that played a fundamental role in the development of the teaching of foreign languages, including speaking, as oral production is only a small segment of the comprehensive process of foreign language teaching and learning, subject to the same laws as the other skills.